Experimental evaluation of composite concrete incorporated with thermal energy storage material for improved thermal behavior of buildings. (15th January 2023) - Singh, Aditya Kumar; Rathore, Pushpendra Kumar Singh; Sharma, R.K.; Gupta, Naveen Kumar; Kumar, Rajan
Abstract: This study shows the effect of integrating eutectic Phase Change Material (PCM) in concrete on thermal, physical, and mechanical properties. Lauric acid and Myristic acid were used to prepare Eutectic PCM. Eutectic PCM was mixed in Zeolite to form Shape Stabilized Composite Phase Change Material (SSCPCM). SSCPCM-39% was found to be most stable and prevents the leakage of the eutectic PCM. SSCPCM-39% was chemical, physically and morphologically stable using Fourier Transform Infrared Spectroscopy (FTIR), X-rays Diffraction (XRD), and Scanning Electron Microscope (SEM). Additionally, SSCPCM-39% possess excellent thermal stability and thermal energy storage capacity which was investigated using Thermo Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). SSCPCM was then integrated in concrete in varying percentage to form Thermal Energy Storage Concrete slab namely TES-C0, TES-C1, TES-C2, TES-C3, and TES-C4. These slabs were then tested in real outdoor environment for thermal behaviour. TES-C4 shows best performance in regulating indoor temperature showing maximum reduction of 14.51% in peak temperature and maximum time delay of 71 min in comparison to TES-C0. Compressive strength of 42 kN, 39 kN, 33 kN, and 29 kN was shown by TES-C1, TES-C2, TES-C3, and TES-C4 respectively after 28 days of hydration process. Highlights: Shape Stabilized Composite Phase Change material (SSCPCM) using eutectic PCM and zeolite was prepared. Maximum 39 wt% of PCM was hold by zeolite without showing any leakage. SSCPCM-39% was thermally, physically, and chemically stable. Maximum reduction of 14.51% in peak temperature and 71 min in time delay achieved.